Technological solutions to guaranteed wage payments of construction workers in China - Kun Huang (International Labour Organization (ILO), 2022)
For many years, wage arrears have been a prevalent problem facing rural migrant workers in the construction sector in China. The difficulties of addressing wage arrears are multifaceted, but are clearly exacerbated by the complex layering of subcontracting that occurs in construction sector. In recent years, China adopted a series of policies and laws to facilitate the timely and full wage payment to migrant workers. With the legal framework in place, central and local governments of China have implemented solutions to improve the efficiency of labour inspection system in addressing wage arrears, thanks to the application of digital technologies. This paper examines how technology was put to use in the design and implementation of an online information platform-National Construction Workers Management and Service Information System - that registers rural migrant workers and ultimately brings them under the realm of public policy to protect them against abuses. The paper examines in detail the Enterprise Wage Payment Online Supervision System (EWPOSS) of Zhejiang Province and analyses how the IT-enabled system has contributed to improving the efficiency of the local labour inspectorates in addressing wage arrears. The paper concludes that digital solutions offer great potential to tackle negative aspects associated to informality if accompanied by adequate policy and legal frameworks, sound digital infrastructure and effective and robust labour inspection systems.
Keywords: 330; migrant workers; minimum wage; construction industry; labour inspection; technology